Anthropogenic Impacts on the Microbial Ecology and Function of Aquatic Environments - Justin R. Seymour (Frontiers Research Topics, 2016)
Aquatic ecosystems are currently experiencing unprecedented levels of impact from human activities including over-exploitation of resources, habitat destruction, pollution and the influence of climate change. The impacts of these activities on the microbial ecology of aquatic environments are only now beginning to be defined. One of the many implications of environmental degradation and climate change is the geographical expansion of disease- causing microbes such as those from the Vibrio genus. Elevating sea surface temperatures correlate with increasing Vibrio numbers and disease in marine animals (e.g. corals) and humans. Contamination of aquatic environments with heavy metals and other pollutants affects microbial ecology with downstream effects on biogeochemical cycles and nutrient turnover. Also of importance is the pollution of aquatic environments with antibiotics, resistance genes and the mobile genetic elements that house resistance genes from human and animal waste. Such contaminated environments act as a source of resistance genes long after an antibiotic has ceased being used in the community. Environments contaminated with mobile genetic elements that are adapted to human commensals and pathogens function to capture new resistance genes for potential reintroduction back into clinical environments. This research topic encompasses these diverse topics and describes the affect(s) of human activity on the microbial ecology and function in aquatic environments and, describes methods of restoration and for modelling disturbances.